The 9-item Academic Self-Efficacy (ASE) scale: validity, reliability and measurement invariance across sexes and six Arab nations - Ali Hemade; Diana Malaeb; Amthal Alhuwailah; Mai Helmy; Muna Barakat; Rabih Hallit; Sami El Khatib; Mohamad Rahal; Syed Arman Rabbani; Reem Alzayer; Nada H. Farrag; Rita El Hajjar; et al. (Scientific Reports)
Abstract Academic self-efficacy (ASE), the belief in one’s ability to succeed in academic tasks, plays a crucial role in student motivation, learning, and performance. Reliable measurement of this construct is essential for identifying students’ strengths and areas for improvement. This study aims to translate and validate the Academic Self-Efficacy Scale for use among university students from six different Arab countries. Using the Snowball sampling technique, participants (n = 2131), university students six Arab countries (i.e., KSA, UAE, Egypt, Lebanon, Oman, and Kuwait), answered the demographic questions and completed the Arabic Academic Self-Efficacy Scale, the Depression Anxiety Stress Scale-8, and the Multidimensional Social Support Scale. Confirmatory Factor Analysis proved a one-factor solution for the ASE scale. Adequate composite reliability was found (ω =.96; α =.96). Convergent and concurrent validity was assessed and proven by a negative correlation with measures of psychological distress and positive correlation with measures of social support. Our translation of the ASE scale was invariant across sexes and countries, with females scoring significantly higher than males. Our Arabic version of the ASE scale is a validated and reliable tool for assessing ASE in Arabic speaking populations, and shall provide means for assessing students’ confidence in their academic abilities and help improve student support.